The Design Blueprint for a Large-Scale Telehealth Platform - Rattakorn Poonsuph (International Journal of Telemedicine and Applications)
Technological innovation plays a crucial role in digital healthcare services. A growing number of telehealth platforms are concentrating on using digital tools to improve the quality and availability of care. Virtual care solutions employ not only advanced telehealth technology but also a comprehensive range of healthcare services. As a result, these can reduce patient healthcare costs as well as increase accessibility and convenience. At the same time, the healthcare service provider can leverage healthcare professionals to get a better perspective into the needs of their patients. The objective of this research is to provide a comprehensive design blueprint for a large-scale telehealth platform. Telehealth is the digital healthcare service combining online services and offline access for healthcare facilities to offer various healthcare services directly to patients. This design blueprint covers the digital healthcare ecosystem, new patient journey design for digital health services, telehealth functionality design, and an outline of the platform infrastructure and security design. Ultimately, telehealth platforms establish a completed digital healthcare service and new ecosystem that provides better care for every patient worldwide.